Primary adjunctive corticosteroid therapy is associated with improved outcomes for patients with Kawasaki disease with coronary artery aneurysms at diagnosis. Issue 3 (17th September 2020) - Friedman, Kevin G; Gauvreau, Kimberlee; Baker, Annette; Son, Mary Beth; Sundel, Robert; Dionne, Audrey; Giorgio, Thomas; De Ferranti, Sarah; Newburger, Jane W
Abstract : Objective: Patients with Kawasaki disease (KD) with coronary artery enlargement at diagnosis are at the highest risk for persistent coronary artery aneurysms (CAAs) and may benefit from primary adjunctive anti-inflammatory therapy beyond intravenous immunoglobulin (IVIG). We evaluate the effect of primary adjunctive corticosteroid therapy on outcomes in patients with CAA at diagnosis. Design: Single-centre, retrospective review. Patients: Patients with KD diagnosed within 10 days of fever onset and with baseline CA z-score ≥2.5. Interventions: Primary treatment with IVIG (n=162) versus IVIG plus corticosteroids (n=48). Main outcome measures: Treatment resistance (persistent fever >36 hours after initial treatment), CAA regression rate. Results: Of the 92 patients with KD who received corticosteroids at our institution from 2012 to 2019, 48 met the inclusion criteria for primary adjunctive therapy. The corticosteroid group was younger and had larger baseline CAAs compared with historical controls. Demographics and laboratory values were otherwise similar between groups. The corticosteroid group had a less treatment resistance (4% vs 30%, p=0.003) and a greater improvement in C reactive protein. After adjusting for baseline CA z-score, age and baseline bilateral versus unilateral CAA, the corticosteroid group had a higher odds of (OR 2.77 (1.04, 7.42), p=0.042) and a shorter time to CAA regression (HR 1.94 (1.27, 2.96), p=0.002). Conclusion: Primary adjunctive corticosteroid therapy is associated with decreased initial treatment resistance, greater improvement in inflammatory markers and higher likelihood of CAA regression in patients who have CAA at diagnosis. Multi-centre, randomised controlled trials are needed to confirm the benefits of corticosteroids in patients with CAA at diagnosis and to compare corticosteroids with other adjunctive therapies.